Komunikasi Interpersonal - Citra Anggraini; Denny Hermawan Ritonga; Lina Kristina; Muhammad Syam; Winda Kustiawan (Universitas Dehasen Bengkulu, 2022)
Interpersonal communication is communication between people face to face, each person involved in the communication influences the perception of the other person's communication. This special form of interpersonal communication is dyadic communication. DeVito argues that interpersonal communication is communication that occurs between two people who have a clear relationship, who are connected in some way. The situational perspective says that interpersonal communication specifically observes the interaction of two people who communicate verbally and nonverbally at the same time. interpersonal communication also has a fast feedback rate.